Answer:
x = 2, y = - 1
Explanation:
Given the 2 equations
3x + 4y = 2 → (1)
x = 5y + 7 → (2)
Substitute x = 5y + 7 into (1)
3(5y + 7) + 4y = 2 ← distribute and simplify left side
15y + 21 + 4y = 2
19y + 21 = 2 ( subtract 21 from both sides )
19y = - 19 ( divide both sides by 19 )
y = - 1
Substitute y = - 1 into (2) for corresponding value of x
x = 5(- 1) + 7 = - 5 + 7 = 2
As a check
Substitute x = 2, y = - 1 into the left side of (1)
3(2) + 4(- 1) = 6 - 4 = 2 = right side
Solution is x = 2, y = - 1